2017
DOI: 10.1016/j.firesaf.2017.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Measuring fuel transport through fluorocarbon and fluorine-free firefighting foams

Abstract: A flux chamber was designed to measure the transient fuel transport through a foam layer before significant degradation of foam occurred. The fuel transport rate through AFFF (fluorinated foam) was much slower than through RF6 (fluorine-free foam) with breakthrough times being 820 s and 276 s respectively over n-heptane. The fuel flux through AFFF covering three fuel pools (n-heptane, iso-octane, and methyl-cyclohexane) was also measured. AFFF had the smallest flux over iso-octane with a breakthrough time over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…In using firefighting agents, environmental safety is an important criterion. The development of environmentally friendly firefighting foams and agents and their effectiveness on both building and wildland fires have been investigated by several authors (Kennedy et al 2015;Hinnant et al 2017;Rakowska et al 2017;Hinnant et al 2020;Rivai et al 2020;Subekti et al 2020). Foam suppression acts by smothering the smouldering, covering the surface of the fuel with a foam layer that prevents oxygen from accessing the fuel.…”
Section: Suppressant Agents To Fight Wildfiresmentioning
confidence: 99%
“…In using firefighting agents, environmental safety is an important criterion. The development of environmentally friendly firefighting foams and agents and their effectiveness on both building and wildland fires have been investigated by several authors (Kennedy et al 2015;Hinnant et al 2017;Rakowska et al 2017;Hinnant et al 2020;Rivai et al 2020;Subekti et al 2020). Foam suppression acts by smothering the smouldering, covering the surface of the fuel with a foam layer that prevents oxygen from accessing the fuel.…”
Section: Suppressant Agents To Fight Wildfiresmentioning
confidence: 99%
“…3 To date, a significant emphasis has been placed on transport through a foam layer, were measured in the absence of a fire and were used to qualitatively explain the causes for differences in fire suppression among foams generated from different surfactant formulations. [7][8][9][10][11][12][13] Hinnant et al 13 examined the differences in a 19-cm diameter pool fire extinction experiment among foams generated from a fluorosufactant (Capstone 1157) and their mixtures with hydrocarbon surfactants (Glucopon 215UP and TritonX 100) for heptane fuel. They showed that measured differences in foam spread, foam degradation, and fuel transport rates on a hot heptane pool explained the differences in heptane fire extinction between Capstone and its mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The variation of fuel affects both fuelfoam interactions and aqueous film formation. The structural variation can cause differences in van der Walls interactions with the surfactant tail at the bubble lamellae in the foam and may lead to differences in foam degradation, 10 fuel transport, 7 foam spread on the pool surface, and fire extinction. These interactions are expected to be different from previous a study, which varied surfactant formulations over a…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorotelomers are the active substance within firefighting foam formulations that cause improved spreading and fire suppression (Donaldson 2016). Certainly, firefighting occurs in many scenarios, but they are all linked to other petroleum-based substances such as diesel, kerosene, and other fuels, hence causing a much more complex co-contamination in the environment (Vecitis et al 2009;Hinnant et al 2017).…”
Section: Introductionmentioning
confidence: 99%